The impact of artificial intelligence on military defence and security - Daniel Araya; Meg King (Centre for International Governance Innovation (CIGI), 2022)
The twenty-first century is now being shaped by a multipolar system characterized by techno-nationalism and a post-Bretton Woods order. In the face of a rapidly evolving digital era, international cooperation will be critical to ensuring peace and security. Information sharing, expert conferences and multilateral dialogue can help the world's nation-states and their militaries develop a better understanding of one another's capabilities and intentions. As a global middle power, Canada could be a major partner in driving this effort. This paper explores the development of military-specific capabilities in the context of artificial intelligence (AI) and machine learning. Building on Canadian defence policy, the paper outlines the military applications of AI and the resources needed to manage next-generation military operations, including multilateral engagement and technology governance.
Keywords: 330